Hubungan antara Pengendalian Produksi dengan Pengendalian Kualitas - Tommy Setiawan Ruslim; M. Yudha Gozali (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
This study aims to determine whether there is a relationship between production control with quality control in PT X. Variables used in production control and quality control. The data used is the data in 2011. Data collection technique used are questionnaire. Data analysis techniques using a simple correlation method. The analysis concludes that there is a relationship between control of production with quality control in PT X.Keywords: Production Control, Quality Control, Simple Regression